1986
DOI: 10.1177/028418518602700412
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vessels and Contrast Enhancement of Hepatocellular Carcinoma Demonstrated by Percutaneous Transhepatic Portography

Abstract: A patient with an Edmondson type I-II hepatocellular carcinoma had, at celiac angiography, a poor arterial supply but a rich portal supply as observed at percutaneous transhepatic portography, an observation not previously reported in this disease. The importance of demonstrating the vascular supply of the tumor previous to planned intravascular treatment is obvious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In one paper, enlarged portal veins were recognized histopathologically in an adenomatous hyperplasia shown as high attenuation on CTAP 23 . Fujisawa et al 28 . reported that a histologically advanced HCC measuring 5 cm was demonstrated as a hypervascular lesion on percutaneous transhepatic portography.…”
Section: Discussionmentioning
confidence: 99%
“…In one paper, enlarged portal veins were recognized histopathologically in an adenomatous hyperplasia shown as high attenuation on CTAP 23 . Fujisawa et al 28 . reported that a histologically advanced HCC measuring 5 cm was demonstrated as a hypervascular lesion on percutaneous transhepatic portography.…”
Section: Discussionmentioning
confidence: 99%